Aerodynamic investigation on compact variable compressor for vehicular turbochargers. Issue 1 (1st April 2022) - Yonemura, Atsushi; Sakisaka, Ryota; Kaneko, Yudai; Morita, Isao; Nagao, Kenichi; Bamba, Takahiro
Abstract: In order to install a turbocharger which has wider operating range and higher boost pressure than a current supercharging system to an internal combustion engine (ICE) and a hybrid vehicle (HV), one development focus lies on a variable trim compressor (VTC) which can change passage area upstream a compressor wheel. In this paper, a new variable geometry device which was developed from the VTC mechanism proposed by Fujiwara et al. in 2018 is studied. The experimental result confirmed the performance enhancement associated with the design concept change and the improvement of trim actuation. In addition, the effect of the throat area ratio as design parameter in the new device on performance was numerically analysed. As a result, the optimal design value of passage area size in the VTC was around 60% and the passage area change position should be placed as close as possible to the compressor wheel.